ANALYSIS OF CABLE NETWORK READINESS FOR THE IMPLEMENTATION OF ENTERPRISE RESOURCE PLANNING INFORMATION SYSTEMS AT THE FACULTY OF INDUSTRIAL ENGINEERING - Akbar febriyanto; Umar Yunan Kurnia Septo Hediyanto; Muhammad Fathinuddin (JIKO (Jurnal Informatika dan Komputer), 2024)
With the rapid advancement of information and communication technology, organizations increasingly adopt integrated systems to enhance efficiency and productivity. One widely adopted technology is Enterprise Resource Planning (ERP), a comprehensive management system that integrates various business functions, including finance, manufacturing, inventory, and human resources. Implementing an ERP system requires a robust network infrastructure, particularly in terms of quality of service (quality of service). This study aims to evaluate the readiness of the cable network infrastructure across three buildings at the Faculty of Industrial Engineering, Telkom University, to implement an Odoo-based ERP system. The research employs the Network Development Life Cycle (NDLC) methodology, focusing on crucial quality of service parameters such as throughput, delay, jitter, and packet loss. Data were collected through observations, interviews, and network analysis using Wireshark, with tests conducted at different times (low, peak, and intermediate). The results show that the TULT Building, Mangudu Building, and Building B Cacuk networks are generally prepared for ERP implementation. For instance, in the TULT Building, the average throughput without filters at low, peak, and intermediate times was 45.296 Kbps, 50.923 Kbps, and 61.399 Kbps, respectively. Packet loss averaged 0.56%, 0.50%, and 0.65% without filters. Despite jitter values ranging from 103.73 ms to 582.40 ms, below the TIPHON standard, the ERP system remains functional as it is not highly sensitive. The study concludes that the existing network infrastructure is sufficient mainly for the Odoo-based ERP implementation, with recommendations for further improvements to address jitter issues.